Synchronous Pancreatic and Rectal Carcinoma in the Same Patient: Case Report and Review of the Literature - Triantafillidis, John K.; George, Malgarinos; Costas, Vagianos; Apostolos, Papalois E. (Archives of Clinical and Medical Case Reports, 2020)
We report a patient with an exceptionally rare combination of synchronous pancreatic and rectal cancer diagnosed within a 4 months’ interval. A 69-year-old female was evaluated for continuous epigastric pain and anorexia over the last three months. The tumor was classified as non-operable, as infiltration of large vessels was detected. The patient responded well to chemo/radiotherapy. However, infiltration of the large vessels was persisted. Four months later the patient started complaining of tenesmus and bloody stools. A digital rectal examination revealed the presence of a mass starting 7-8cm from the anal margin. Sigmoidoscopy showed a mass protruding into the bowel lumen. The patient died 16 months after the diagnosis of pancreatic cancer and 12 months after the diagnosis of rectal cancer. We suggest that clinicians should be aware about the possibility of the existence of multiple primary tumors in the same patient and subsequently to optimize their investigational plans.